Advanced Urban Trees. How street trees can be part of the solution. An advanced system of urban tree pits to be included in decentralized stormwater management. - Biber, Carmen (My University, 2018)
Urban trees can be part of the solution in terms of urban development and stormwater management within climate change: increasing the biodiversity of urban nature and reconnect citizens to nature, protecting the urban surfaces against heat and using stormwater in the natural water cycle. Cities will benefit economically, ecologically, socially and visually from vital urban trees.
Keywords: Umweltschutz; Regenwasser; Hochwasser; Regenwassermanagement; Naturnähe; Straßenraumgestaltung; Straßenbaum; Stadtbaum; Bepflanzung; Erdboden; Technische Anlage; Schacht; Untergrund; Bewässerung